STRATEGI PENANAMAN KARAKTER RELIGIUS MELALUI PEMBIASAAN KEAGAMAAN PADA PESERTA DIDIK KELAS 1 SD NEGERI 01 GANTIWARNO TAHUN PELAJARAN 2024/2025 - Aulia Raudah Alima; Anita Trisiana; Sarafuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the strategies used to develop religious character in first-grade students at SD Negeri 01 Gantiwarno. Religious character is considered a crucial dimension in strengthening character education at the elementary school level, serving as the foundation for shaping children’s personalities from an early age. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The strategies identified involve structured habituation of religious activities, such as communal prayers before and after lessons, regular Quran recitation (tadarus), congregational prayers, and celebrations of Islamic holidays. Additionally, the role of teachers as role models and the support of a religious school environment significantly reinforce the internalization of religious values. These habitual practices contribute to the comprehensive development of students’ character, encompassing cognitive, affective, and psychomotor aspects. In conclusion, the strategies implemented at SD Negeri 01 Gantiwarno have proven effective in systematically and sustainably shaping the religious character of its students.